The Impact of Vertical Fiscal Imbalance and Local Government Expenditure Structure on the Quality of Economic Development in China : A Study Based on a Simultaneous Equations Model - Ke, Wang; Venus Liew, Khim Sen (International Journal of Economics and Financial Issues (EJEFI), 2025)
The challenge of improving economic development quality and achieving sustainable growth has become a pressing issue for the Chinese government. This study explores the interaction between vertical fiscal imbalance, local government expenditure structure, and economic development quality. Using panel data from 30 Chinese provinces spanning 2008-2022, the study applies the three-stage least squares method to assess the dual impact of vertical fiscal imbalance on economic development quality. The results demonstrate that vertical fiscal imbalance not only has a direct negative impact on economic development quality but also indirectly impairs it by constraining the expenditure structure. Moreover, local government expenditure on public welfare projects plays a pivotal role in improving economic development quality. This study highlights the importance of addressing vertical fiscal imbalance in improving economic development quality. It recommends a rational division of fiscal powers and responsibilities between central and local governments, reforms to China’s fiscal transfer payment system, and optimization of the expenditure structure to mitigate vertical fiscal imbalance and enhance China’s economic development quality.